Explaining the rising precariat in Spain - de la Poza, Elena; Jodar, Lucas; Merello, Paloma; Todoli-Signes, Adrián (Technological and Economic Development of Economy, 2020)
Spanish GDP indicator figures recover while the risk of poverty has not stopped increasing since 2007 given the continuous austerity policies adopted by Governments, while labour and welfare conditions have worsened. A new phenomenon is emerging: the flattening of the Spanish middle class. This study proposes a model to quantify the number of individuals according to their level of precariousness in Spain. The model allows us to predict the behaviour of society in Spain given the mimetic nature of humans by constructing a discrete finite epidemiological model that classifies and quantifies the population in Spain according to its risk of precariousness. Our results show a rise in the precariat of 3% (representing 39% of the total population at the end of the study). The relevance of this study lies in providing measures to governments that can mitigate the negative effects of this problem and stop its growth. Indeed tax measures to help firms to distribute their profits among employees and measures engaging a labour reform to establish limits to the rate of temporary jobs and working overtime should be considered.